PENGARUH KEMUDAHAN PENGGUNAAN TOKOPEDIA TERHADAP PEMBAYARAN UANG KULIAH: TINJAUAN PUSTAKA: Pengaruh Kemudahan Penggunaan Tokopedia terhadap Pembayaran Uang Kuliah: Tinjauan Pustaka - Febi Julia Ariska; Elida Elfi Barus (Program Studi Ekonomi Syariah, 2025)
This study aims to examine the effect of the ease of use of Tokopedia on tuition payments in Indonesia, focusing on implementing digital payment systems such as QRIS and electronic wallets. This literature review identifies various benefits Tokopedia provides as a tuition payment platform, including ease in the transaction process, flexibility of payment methods, and increased administrative efficiency in educational institutions. Tokopedia, with the integration of the QRIS system, allows students to make payments using various e-wallets, which speeds up the process and increases financial inclusion among students, especially those living in remote areas. However, while the platform provides convenience, data security and economic inclusion challenges are still a significant concern. Transaction security, especially in terms of the protection of users' personal data and accessibility for students who do not have adequate access to digital technology, is an issue that needs to be addressed. In addition, Tokopedia also improves students' financial literacy, helps them manage their expenses, and prepares them for future financial challenges. Overall, Tokopedia has made an essential contribution to the digitization of tuition payments, but economic security and inclusion challenges must continue to be considered to optimize its benefits.